2015
DOI: 10.1177/0959683615584208
|View full text |Cite
|
Sign up to set email alerts
|

Evidences for centennial dry periods at ~3300 and ~2800 cal. yr BP from micro-facies analyses of the Dead Sea sediments

Abstract: Laminated lake sediments from the Dead Sea basin provide high-resolution records of climatic variability in the eastern Mediterranean region, which is especially sensitive to changing climatic conditions. In this study, we aim on detailed reconstruction of climatic fluctuations and related changes in the frequency of flood and dust deposition events at ca. 3300 and especially at 2800 cal. yr BP from high-resolution sediment records of the Dead Sea basin. A ca. 4-m-thick, mostly varved sediment section from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 89 publications
2
46
0
Order By: Relevance
“…These again suggest drier conditions than the millennialaverage, and the presence of non-varved sediments for the first of these periods could be taken to indicate an even drier climate than in the interval~4300e4150 years BP. The period~3150e2550 years BP is synchronous within dating uncertainty with a drought seen across the Eastern Mediterranean (Roberts et al, 2001;Verheyden et al, 2008;Langgut et al, 2013;Neugebauer et al, 2015), at the time of the so-called Late Bronze Age Collapse/Crisis (Kaniewski et al, 2013) when civilisations such as the Hittites in central Turkey went into decline (Weiss, 1982;Akurgal, 2001). The period 2500e2300 years BP could be coincident with some peaks seen in the Eski Acıg€ ol d 18 O carbonate record, but more high-resolution records from the region are required to help establish if there was a widespread excursion to increasing dryness at this time.…”
Section: Centennial-scale 'Events' In the Mid To Late Holocenementioning
confidence: 97%
“…These again suggest drier conditions than the millennialaverage, and the presence of non-varved sediments for the first of these periods could be taken to indicate an even drier climate than in the interval~4300e4150 years BP. The period~3150e2550 years BP is synchronous within dating uncertainty with a drought seen across the Eastern Mediterranean (Roberts et al, 2001;Verheyden et al, 2008;Langgut et al, 2013;Neugebauer et al, 2015), at the time of the so-called Late Bronze Age Collapse/Crisis (Kaniewski et al, 2013) when civilisations such as the Hittites in central Turkey went into decline (Weiss, 1982;Akurgal, 2001). The period 2500e2300 years BP could be coincident with some peaks seen in the Eski Acıg€ ol d 18 O carbonate record, but more high-resolution records from the region are required to help establish if there was a widespread excursion to increasing dryness at this time.…”
Section: Centennial-scale 'Events' In the Mid To Late Holocenementioning
confidence: 97%
“…A multi proxy study is essential to define if a sediment archive is useful as climate archive and endorheic lakes have shown to be very sensitive to climate changes (Laird et al, 1996;Beklioglu et al, 2007;Davis and Stevenson, 2007;H€ obig et al, 2016), despite of possible difficulties in climate information (Lane et al, 2013), which have been verified within this study. A comparison to other Iberian lake studies (Frigola et al, 2007;Corella et al, 2010;Martín-Puertas et al, 2011;Moreno et al, 2012;Valero-Garc es et al, 2006H€ obig et al, 2016) is difficult (Magri et al, 2004), as for example the elements and ratios measured and obtained by XRF data depends on the geological setting and catchment area as well as sediment transport (Talbot and Allen, 1996;Lopez et al, 2006). However, climate records are often synchronized, disregarding spatial patterns and temporal transgressive differences (Giralt et al, 1999;Lane et al, 2013).…”
Section: Interpretation and Conclusionmentioning
confidence: 93%
“…In our study we have chosen a lake as paleoclimate archive, because (i) former studies have shown that lacustrine sediments in Southern Spain can provide high-resolution information of past environments (e.g. Reed et al, 2001;Valero-Garc es et al, 2006;Martín-Puertas et al, 2010;Anderson et al, 2011;Giralt et al, 2011;Martín-Puertas et al, 2011;Moreno et al, 2012;H€ obig et al, 2016), (ii) sedimentation rates in lakes are usually higher than those in the ocean (Cohen, 2003) and, (iii) shallow endorheic salt lakes can be very sensitive to climate changes (Laird et al, 1996;Beklioglu et al, 2007;Davis and Stevenson, 2007;H€ obig et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) comprises greenish detrital laminae containing green algae remains and represents highest lake levels and less salty lim- Figure 5. Comparison of the Dead Sea to other records: (a) the relative Dead Sea lake level curve inferred from micro-facies analysis of the deep-basin core 5017-1 (this study; right y axis) and from site PZ-7 from the Perazim Valley (dashed line; left y axis, indicating maximum or minimum relative lake levels; Waldmann et al, 2009); (b) sum of normalised ratios of Ca / (Sr+S) and Ti / Ca as proxies for carbonate and siliciclastic detritus, respectively, and of Sr / Ca, proxy for aragonite, subtracted by the Cl / Br ratio, which is a proxy for halite, [Ca / (Sr+S) + Ti / Ca + Sr / Ca -Cl / Br] indicating the water balance of the lake and agreeing well with the relative lake level curve; (c) mean summer (JJA) insolation at 30 • N (after Laskar et al, 2004); (d) δ 18 O of Soreq and Peqin speleothems, Israel (Bar-Matthews et al, 2003), and eastern Mediterranean sapropel events S3 and S4 (according to Bar-Matthews et al, 2000); (e) humidity index of continental North Africa (core GeoB7920-2) and "green Sahara" phases (Tjallingii et al, 2008); (f) Monticchio (southern Italy) pollen record of mesic woody taxa and Mediterranean pollen zones Melisey (M) I and II, and St. Germain I and II (Brauer et al, 2007;Martin-Puertas et al, 2014) -note a possible chronological shift of 3500 years to the older for 92-76 ka according to Martin-Puertas et al (2014); (g) Greenland ice core δ 18 O record on GICC05 modelext timescale (Wolff et al, 2010) -also indicated are Greenland interstadials (GI) after Rasmussen et al (2014) and North Atlantic ice-rafting events C21 to C24 (Chapman and Shackleton, 1999). Marine isotope stages are given according to Wright (2000).…”
Section: Micro-facies As Relative Lake Level Indicatorsmentioning
confidence: 99%